Mua - Gomes, Jenny (Te Kaharoa, 2019)
1.39 am 32 year old Private investigator Marama Walker squinted at the road ahead trying to see past the battering rain pelting against her windscreen. Huddling closer to the steering wheel, she absently pushed a wayward lock of wavy black hair with one hand and steered with the other. As the wind picked up outside, she wondered what the gods were trying to tell her. After all, it’s been years since she quit her job as a cop and became a private investigator. A decision made at an impulse after the death of her daughter five long years before. It came as a shock when the Chief of police demanded she meet him tonight. Looking at the time she couldn’t help but think just what was so urgent that her former boss the Chief of police sought her out after half a decade. Marama couldn’t help but grimace at the thought a niggling feeling of foreboding creeping on the back of her mind. Marama fumbled around the front of her shirt until she felt the touch of a smooth stone, a pounamu touched her finger. Marama often did this to remember who she used to be. Sighing she let go and forged ahead towards her destiny.